2015
DOI: 10.1186/s12902-015-0049-7
|View full text |Cite
|
Sign up to set email alerts
|

Marginal structural models for the estimation of the risk of Diabetes Mellitus in the presence of elevated depressive symptoms and antidepressant medication use in the Women’s Health Initiative observational and clinical trial cohorts

Abstract: BackgroundWe evaluate the combined effect of the presence of elevated depressive symptoms and antidepressant medication use with respect to risk of type 2 diabetes among approximately 120,000 women enrolled in the Women’s Health Initiative (WHI), and compare several different statistical models appropriate for causal inference in non-randomized settings.MethodsData were analyzed for 52,326 women in the Women’s Health Initiative Clinical Trials (CT) Cohort and 68,169 women in the Observational Study (OS) Cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…These results also suggest that physical activity may have different biologic effects on each RA subphenotype. An alternative strategy for the mediation analysis would be to perform analyses using marginal structural models, but previous literature suggests that a marginal structural model would produce findings similar to those obtained with our approach . Our findings add to the literature demonstrating differences based on BMI and other measures of adiposity for RA risk by serologic phenotype .…”
Section: Discussionsupporting
confidence: 74%
“…These results also suggest that physical activity may have different biologic effects on each RA subphenotype. An alternative strategy for the mediation analysis would be to perform analyses using marginal structural models, but previous literature suggests that a marginal structural model would produce findings similar to those obtained with our approach . Our findings add to the literature demonstrating differences based on BMI and other measures of adiposity for RA risk by serologic phenotype .…”
Section: Discussionsupporting
confidence: 74%
“…Thus, 17 papers met our selection criteria. Two papers reported results from more than one study [ 23 , 24 ]; the reported estimates of the single studies used by Pan and Frisard were used in the present analysis. Thus, 20 estimates were included in the main analysis ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies previously included in the meta-analyses of Yoon and Bhattacharjee were excluded from the present review [ 7 , 8 ]. For two of these studies updated results were available [ 10 , 24 ], and thus they were included in our meta-analysis instead of the old ones [ 25 , 26 ]. The remaining three studies were excluded because one was restricted to children and adolescents [ 27 ], one had a cross-sectional design [ 28 ] and the last one was based on spontaneous reports of hyperglycemia rather than on new-onset diabetes [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact biological mechanisms underlying the relationship between depressive symptoms, sleep disturbances, and T2DM are not well understood. 39 However, evidence suggests that both depression and sleep disturbances may hinder glycemic control by causing deregulation of the hypothalamic-pituitary-adrenal (HPA) axis. Specifically, depression 40,41 and disturbed sleep 42 are associated with increased secretion of cortisol.…”
Section: Discussionmentioning
confidence: 99%